Rural Agribusiness Business Development Strategy In Increasing Farmers' Income (Case Study Of Joint Farmer Group In Deli Serdang) - Nasution, Husairi Muhammad; Batubara, Maryam; Arif, Muhammad (UNIVERSITAS PAKUAN, 2022)
Development of Rural Agricultural Activities (PUAP) is one of the programs developed by the Ministry of Agriculture to be implemented in an integrated manner with the National Community Empowerment Program (PNPM-M). The purpose of this research is to answer the following problems: Describe Gapoktan strategies in the Rural Agribusiness Development Program (PUAP) and determine the impact of the Rural Agribusiness Development Program (PUAP) activities in increasing farmers' income in Deli Serdang. The method used in this study is a census where the data obtained are primary data and secondary data. Primary data is data collected directly from interviewed farmers. This study uses descriptive analysis to provide an overview of the implementation of the Rural Agricultural Business Development Program (PUAP) for rice cultivation in Deli Serdang Regency. Gapoktan PUAP Performance Assessment. The results of this study are the level of effectiveness of the results of research on the implementation of the Rural Agricultural Business Development Program (PUAP) on Gapoktan performance. When the income exceeds the total cost, then part of the farmer's income is generated by a combination of farmer groups (gapoktan) before and after receiving funds from the Rural Agricultural Business Development Program (PUAP), which has a t-score of -14.126 and has a significance of 0.000 lt; 0.05, Hi received. The results of this study are the level of effectiveness of the results of research on the implementation of the Rural Agricultural Business Development Program (PUAP) on Gapoktan performance. When the income exceeds the total cost, then part of the farmer's income is generated by a combination of farmer groups (gapoktan) before and after receiving funds from the Rural Agricultural Business Development Program (PUAP), which has a t-score of -14.126 and has a significance of 0.000 lt; 0.05, Hi received. The results of this study are the level of effectiveness of the results of research on the implementation of the Rural Agricultural Business Development Program (PUAP) on Gapoktan performance. When the income exceeds the total cost, then part of the farmer's income is generated by a combination of farmer groups (gapoktan) before and after receiving funds from the Rural Agricultural Business Development Program (PUAP), which has a t-score of -14.126 and has a significance of 0.000 lt; 0.05, Hi received